A novel method for trans-pyloric feeding in a premature newborn following repair of congenital duodenal obstruction - Erika B. Lindholm, M.D; Meade Barlow, M.D; Nate Heinzerling, M.D; Andrew Hong, M.D (Elsevier, 2017)
We present a case of a newborn premature infant with duodenal stenosis and a significant cardiac abnormality who required early operative intervention due to failure to thrive on parenteral nutrition. A novel method of post-operative feeding was employed utilizing a transanastomotic feeding tube placed through a Malecot gastrostomy tube. The advantages of the procedure are discussed.